A preliminary list of the Pyraloid moths (Lepidoptera: Pyraloidea) of Kyrgyzstan - Sinev, Sergey Yu.; Korb, Stanislav K. (Zootaxa, 2022)
A preliminary list of the pyraloid moths of Kyrgyzstan is provided. In total, 264 species are mentioned for this country, among them 117 listed by literature data and 146 species recorded in current paper for the first time. Another 97 species are known from the neighboring territories and most probably are also present in Kyrgyzstan.